From nematode to Nobel: How community-shared resources fueled the rise of Caenorhabditis elegans as a research organism - Victor R. Ambros; Martin Chalfie; Aric L. Daul; Andrew Z. Fire; David H. Hall; H. Robert Horvitz; Craig C. Mello; Gary Ruvkun; Nathan E. Schroeder; Paul W. Sternberg; Ann E. Rougvie (Proceedings of the National Academy of Sciences, 2025)
Experimental organisms such as the nematode Caenorhabditis elegans are fundamental to biological discovery. The success of C. elegans research has been greatly enabled by infrastructure that allows thousands of scientists to share and access research materials and unpublished information efficiently. Here, we celebrate the worm by interweaving vignettes describing four Nobel Prize–winning discoveries with descriptions of how the major NIH-supported research resources—the Caenorhabditis Genetics Center, WormBase, and WormAtlas—provide invaluable support for all C. elegans research. The synergy between investigation and the availability of shared resources for the C. elegans community is a paradigm for all model organism research, and the continued support of such community research resources will be essential for maximizing impactful discoveries in the future.